Vascularized in vitro bone model as 3D quadruple culture with primary human osteoblasts, osteocytes, osteoclasts and endothelial cells - Katharina Wirsig; Nina Bürger; Lisa Fleischhauer; Nele Louisa Preuß; Anne Bernhardt (Materials Today Bio)
With an aging population worldwide, research into bone metabolism and novel therapies for damaged and diseased bone is essential. Bone is a vascularized, dynamic tissue that undergoes a constant remodeling process mediated by osteocytes, osteoblasts and osteoclasts. In this study, a complex 3D in vitro bone model combining these three main bone cell species with endothelial cells was developed. The different cell species were isolated from primary human tissue and spatially arranged using transwell inserts. Osteocytes differentiated from collagen-embedded osteoblasts, while osteoclasts simultaneously derived from peripheral blood mononuclear cells without receptor activator of NF-κB ligand (RANKL) supplementation. Different cultivation parameters were evaluated to define conditions that support differentiation and function of all cell types involved in quadruple culture. The cellular crosstalk in quadruple cultures stimulated osteoblast (ALP, BMP-2, IBSP, COL1A, VEGF) and osteocyte (SOST, DMP1) markers, while osteoclast (TRAP) and endothelial cell markers were reduced compared to respective mono- or co-cultures. Furthermore, mineralization was induced only in quadruple cultures, demonstrating the importance of signaling between the four cell types. This sophisticated human bone model provides a physiologically relevant culture system to study the complex crosstalk between bone cells, their precursors and endothelial cells during remodeling and vascularization. Moreover, it allows preclinical testing of bioactive factors, biomaterial extracts or drugs for translation into clinical practice without animal testing.